Obesity and Gynecologic Malignancies: A Narrative Review of Molecular Mechanisms and Clinical Management Challenges - Bessmylna, Kateryna; Chrobak, Agata; Żukowska, Joanna Katarzyna; Kravets, Alesia; Zhukava, Lizaveta; Alansi, Abdulrahman; Weng, Kai-Chiun; Volkava, Darya; Sakovich, Volha; Kacynel, Ewa; Myślicka, Wiktoria (Quality in Sport, 2026)
Background. Obesity has reached epidemic proportions and is considered a primary risk factor for gynecologic malignancies. Its evolving influence, aligned with modern molecular classifications, demands a reassessment of clinical strategies. Aim. This narrative review integrates evidence on the molecular mechanisms linking obesity to gynecologic cancers and evaluates the impact on clinical management and clinical outcomes. Material and Methods. A literature search of PubMed and Google Scholar (2018–2026) was conducted. Thirty one peer-reviewed articles were selected for qualitative synthesis, focusing on molecular pathophysiology and clinical management. Results. Adipose tissue promotes carcinogenesis via insulin resistance, chronic inflammation, and estrogen dysregulation. In endometrial cancer, obesity is a primary etiologic factor linked to MMRd (mismatch repair deficiency) and NSMP (no specific molecular profile) molecular subtypes (FIGO 2023). In ovarian cancer, visceral adiposity establishes an omental metastatic niche through lipid-mediated metabolic crosstalk and fatty acid b-oxidation. In cervical cancer, obesity acts as an indirect risk factor by compromising screening participation and diagnostic visualization. Clinical management is challenged by surgical technicalities and chemotherapy dosing dilemmas. Emerging data suggest an “obesity paradox”, where inflammatory environments may paradoxically enhance responses to immune checkpoint inhibitors in specific molecular cohorts. Conclusions. Managing this population requires a shift toward precision metabolic oncology. Future strategies have to prioritize assessing visceral adiposity and integrating metabolic interventions, such as GLP-1 receptor agonists, to improve oncologic outcomes.